IDENTIFIKASI KEARIFAN POLA HIDUP SEHAT (WELLNESS) LOKAL MASYARAKAT DESA WISATA NGLANGGERAN SEBAGAI UPAYA ADAPTASI PROTOKOL CLEAN, SAFETY, HEALTHY, AND ENVIRONMENT (CHSE) - Yosephine Elisabeth Pasaribu; Lastiani Warih Wulandari (Kepariwisataan: Jurnal Ilmiah, 2021)
Postmodern science is frequently insufficient to address problems in the human environment, such as health during a pandemic like the one that exists today. As a result, it is critical to begin seeking a more comprehensive solution to the Covid-19 pandemic, particularly in the tourism business, by applying the CHSE (Clean, Health, Safety and Environment) protocol using traditional local science and knowledge methodologies. This study is part of the Ambarrukmo Tourism Institute (STIPRAM) Yogyakarta student team's community service project, at the Holistic Village Development and Development Program (PHP2D). A descriptive qualitative research approach is used to determine local wellness. The study's findings reveal that some of the community's daily actions reflect the realization and can be incorporated into the CHSE protocol for Tourism Villages.Keywords: Wellness, CHSE Protocol, Nglanggeran, Tourism